(untitled) (EDUCATION IN THE 21ST CENTURY, 2023)
Introduction. The most significant sociocultural aspects that affect teaching Mathematics in primary school and a teacher’s training to teaching Mathematics are studied in the paper. Purpose. The aim of the article is to study the issues of an elementary school teacher’s mathematical training, necessary for the development of pupils’ perceptions of the surrounding world, the formation of key competences, upbringing of socially significant personality traits and sociocultural foundations of being. Results. Analysis of ideas about the surrounding world shows that the most important are ideas about the shapes of objects and the corresponding geometric abstractions of volume and surface figures, as well as such “universals” as a point, line, segment, curve, part of a curve, a closed line, a surface, "accessories", "lie between", etc. relations. It is also noted that the mastery of various kinds of measurements (geometric, physical, economic, social), including appropriate tools and procedures, is of exceptional importance for involving younger schoolchildren in social trends and processes. To teach younger schoolchildren the relevant concepts and procedures, a teacher must have a good mathematical background, providing him/her with knowledge and deep understanding of mathematical and activity nature of processes of measuring values or evaluating certain socio-cultural entities (good – bad, beautiful – ugly, etc.). Superficial ideas about measuring values (and more so about qualitative assessments) serve as an obstacle for ideologically correct conceptual and operational interpretation of approaches, methods and tools used in measuring quantities and qualitative assessments of any entities when comparing them. Originality. Based on the results, it is shown that the modification of the ways in which pupils perceive educational information requires from an elementary school teacher to have such a level of professional pedagogical development that ensures readiness to methodological-and-mathematical adaptation and the ability to determine effective ways to influence students in various educational circumstances. Educational circumstances arising as a result of the influence of information flows of various content and socio-cultural conditions on students’ and, accordingly, teachers’ subject (mathematical) activities require a comprehensive study and development of methods of methodical response, ensuring perceiving the learning material in volumes and terms which are provided by the program (in Mathematics) and scheduling. Conclusion. At the present stage of the sociocultural development of the society and the education system, mastering by an elementary school teacher an ability for perspective vision and essential analysis of trend methodological trends that can serve as the basis for the variability of presentation, perceiving and application of mathematical (or other) concepts is being actualized. At the same time, it remains extremely important that Mathematics should be studied (and taught) in the way this knowledge will be used in the future.